The effects of adult and non-adult mortality on long-run economic development: Evidence from a heterogeneous dynamic and cross-sectionally dependent panel of countries between 1800 and 2010 - Dierk Herzer; Korbinian Nagel; Ralf Dewenter (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2017)
This study examines the effects of adult and non-adult mortality on the long-run level of income in a heterogeneous dynamic and cross-sectionally dependent panel. Employing data for 20 countries between 1800 and 2010, it is found that (i) while non-adult mortality has no long-run effect on GDP per capita, reductions in adult mortality lead to statistically and economically significant increases in the long-run level of per capita income; (ii) there are no significant differences in the long-run effects of adult mortality and non-adult mortality on GDP per capita before and after the onset of the demographic transition; and (iii) mortality in middle adulthood has the greatest impact on economic development, whereas early adulthood mortality and mortality in later adulthood have little to no impact on the long-run level of per capita income.
Keywords: I15; O11; J11; C23; 330; Life expectancy; Adult mortality; Non-adult mortality; Economic development; Heterogeneous panel data models; Cross-sectional dependence; Demographic transition